Islam and Environmental Protection: The Implementation of Ecological Dakwah in the Makassar "Zero Waste" Community - Mz, Ihsan; Marhani, Isnaeni; Andi Halima (Alhadharah: Jurnal Ilmu Dakwah, 2024)
ABSTRACT Efforts to reduce waste need to continue to be declared. This is important because an increase in the amount of waste will have an impact on the environment and lead to numbers of problems in life. The production of waste is influenced by a variety of factors. Among them is an understanding of waste handling and consumer lifestyle. However, there are still groups of people who care about environmental conservation. One of them is the "Zero Waste" community of Makassar. The aim of this research is to find out the implementation of the ecological perspective in the “Zero Waste” community as an effort to preserve the environment and reduce the waste result. The method used is qualitative descriptive, with the use of description analysis on the community. Data collection techniques using interviews and documentation. The results of this research shows that the implementation of ecological perspectives in the “Zero Waste” community includes 1) dakwah bil-lisan, in the form of providing training, becoming speaker and educating the public; 2) dakwah bil-kitabah, promoting waste management through social media communities; and 3) dakwah bil-hal, implementing a “waste fasting” lifestyle and collaborating with related stakeholders such as government and private agencies. KEYWORDS Ecological Dakwah, Environment, Islam, Zero Waste Community